Economic, ecological and genetic impacts of marine stock enhancement and sea ranching: A systematic review. Issue 3 (12th February 2018) - Kitada, Shuichi
Abstract: Hatchery release is one of the most popular management tools in fisheries, forestry and wild life management, while its negative impacts on wild populations are a global concern. Research and monitoring of its impacts are generally lacking, and the usefulness of hatchery release for fisheries and conservation objectives is unclear. Here, I evaluated positive and negative impacts of worldwide marine stock enhancement and sea ranching programmes in a systematic review associated with meta‐analyses with the goal of reducing bias of the review. Vast numbers of individuals of more than 180 species are released into the wild each year, but most studies are at experimental stages to assess its potential, and empirical studies are sparse for evaluating the impact on fishery production. Most cases are economically unprofitable except for a few successful cases or unevaluated. The effects of releasing juveniles can be dwarfed by the magnitude of natural recruitment when the spawning stock produces much larger recruitment than released juveniles. Density‐dependent growth caused by competition of food can be substantial, and growth rates of hatchery and wild fish and other competitive species can simultaneously be reduced when stocking exceeded the carrying capacity. Relative reproductive success can vary depending on the species, seed quality and environmental factors. Empirical studies show evidence of substantial gene flow from hatcheries, but fitness reduction in stocked populations has not been reported. The results represent the current state of worldwide marine stock enhancement and sea ranching activity and provide key information for growing fields of artificial propagation and conservation.